Higher physiological vulnerability to hypoxic exposure with advancing age in the human brain. Issue 2 (February 2020) - Vestergaard, Mark B; Jensen, Mette LF; Arngrim, Nanna; Lindberg, Ulrich; Larsson, Henrik BW
The aging brain is associated with atrophy along with functional and metabolic changes. In this study, we examined age-related changes in resting brain functions and the vulnerability of brain physiology to hypoxic exposure in humans in vivo. Brain functions were examined in 81 healthy humans (aged 18–62 years) by acquisitions of gray and white matter volumes, cerebral blood flow, cerebral oxygen consumption, and concentrations of lactate, N-acetylaspartate, and glutamate+glutamine using magnetic resonance imaging and spectroscopy. We observed impaired cerebral blood flow reactivity in response to inhalation of hypoxic air (p = 0.029) with advancing age along with decreased cerebral oxygen consumption (p = 0.036), and increased lactate concentration (p = 0.009), indicating tissue hypoxia and impaired metabolism. Diminished resilience to hypoxia and consequently increased vulnerability to metabolic stress could be a key part of declining brain health with age. Furthermore, we observed increased resting cerebral lactate concentration with advancing age (p = 0.007), which might reflect inhibited brain clearance of waste products.